Isolation and physical characterization of hydrophobin-like proteins (HLP) from aerial conidia of metarhizium anisopliae var. anisopliae - King, Patricia Jie Hung; Kiong, Diana Siaw Boon; Choon, Fah Josept Bong (Science Publications, 2015)
The aim of this study was to isolate and physically characterized Hyrophobin-Like Proteins (HLP) from the aerial conidia of two local isolates of Metarhizium anisopliae var. anisopliae, namely, TA and LR2. The protein samples were isolated based on their insolubility in hot Sodium Dodecyl Sulfate (SDS). The SDS-insoluble proteins were then purified in cold 98% formic acid and performic acid. The molecular weight of the Formic Acid Extracted (FAE) proteins fell in the range of 13-17 kDa with the contents of 3.80 and 3.56 mg mL-1 for TA and LR2, respectively. Due to the stringent protocol of isolation and purification, the FAE proteins can be verified as Hydrophobin-Like Proteins (HLP). Both the HLP samples isolated from M. anisopliae isolates TA and LR2 have low contact angles of 57.06±0.38 and 58.43±0.25°, respectively. The HLP also revealed good emulsification effect in the oil-water phase. Conidia showed good dispersion in aqueous solution with the application of HLP. Paper pre-coated with HLP resisted wetting by water for up to 439 sec. These unique properties of HLP from local isolates of M. anisopliae var. anisopliae are of great potential to be used in wide range of industrial applications.